Kemampuan Pemecahan Masalah Siswa pada Materi Suhu dan Kalor melalui Experiential Learning Berbasis Fenomena - Prima Warta Santhalia; Lia Yuliati; Hari Wisodo (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This research was aimed to describe problem solving skill in Experiential Learning based on the phenomenon, particularly about heat and temperatur. This study was conducted using mix method approach with embedded experimental model research design. The data were collected through pretest and posttest using test and interview. The result of N-Gain Score calculation showed that there are increase in student’s skill on solving problem about temperature and calorie is in moderate category, and the result of d-cohen effect size is in moderate category. At the same time the result of qualitative calculation on student solving skill showed there are 9,4% students in low category, 53,1% student in medium category, and 37,5% student are in high category after experiencing phenomenon based Experimental Learning. Student’s skill in problem solving has to be practiced more intensively using real-life problem in daily life.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah siswa dalam pembelajaran Experiential Learning berbasis fenomena terutama pada suhu dan kalor. Penelitian ini menggunakan pendekatan mix method dengan desain penelitian embedded experimental model. Data dikumpulkan melalui pretest dan posttest menggunakan tes dan wawancara. Hasil perhitungan N-Gain score menunjukkan adanya peningkatan kemampuan siswa dalam memecahkan suhu dan kalor dalam kategori sedang dan hasil perhitungan d-cohen effect size dalam kategori sedang. Sementara itu, hasil perhitungan kualitatif kemampuan pemecahan masalah siswa melalui crosstabulation menunjukkan sebanyak 9,4% siswa berada pada kategori rendah, 53,1% siswa pada kategori sedang, dan 37,5% siswa pada kategori tinggi setelah mengalami Experiential Learning berbasis fenomena. Kemampuan pemecahan masalah siswa perlu dilatih lebih intensif menggunakan masalah nyata dalam kehidupan sehari-hari.